1983
DOI: 10.1111/j.1699-0463.1983.tb00024.x
|View full text |Cite
|
Sign up to set email alerts
|

Mouse‐protective Effect of Rabbit Anti‐r‐protein Antibodies Against Group B Streptococci Type Ii Carrying R‐protein

Abstract: Linden, V. Mouse-protective effect of rabbit anti-R-protein antibodies against group B streptococci type I1 carrying R-protein. Lack of effect on type 111 carrying R-protein. Acta path. microbiol. immunol.scand. Sect. B, 9 / : 145-151, 1983. R-proteins was isolated by affinity chromatography from an alkaline extract of group B streptococci, type 111. The identity of the protein was demonstrated by pepsin-and trypsin-treatment and in double diffusion-in-gel with antisera from other laboratories. A monospecif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1983
1983
1993
1993

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…We were not able to demonstrate any mouseprotective effect of anti-R-protein antibodies against experimental type 111 infections. On the other hand, such antibodies do protect mice from infection by type I1 strains carrying R-protein ( 13) which might contribute to the low frequency of type I1 strains in neonatal meningitis also reflected in the present report, provided that anti-R antibodies are also protective in human beings. R-protein is generally considered to be ))unstable( (1 5); the meaning of this characterization, as well as the scientific background to such a statement, is not clear.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…We were not able to demonstrate any mouseprotective effect of anti-R-protein antibodies against experimental type 111 infections. On the other hand, such antibodies do protect mice from infection by type I1 strains carrying R-protein ( 13) which might contribute to the low frequency of type I1 strains in neonatal meningitis also reflected in the present report, provided that anti-R antibodies are also protective in human beings. R-protein is generally considered to be ))unstable( (1 5); the meaning of this characterization, as well as the scientific background to such a statement, is not clear.…”
Section: Discussionsupporting
confidence: 59%
“…B and C. For many years it was believed that R-protein was of no importance for the virulence of group B streptococci ( I ) , a view based on the observation that anti-R antibodies are incapable of protecting mice against infection by group A streptococci type 28 (1 2). Recently, we demonstrated that anti-R antibodies are in fact capable of protecting mice from infection by type I1 group B streptococci carrying this antigen, but not against type I1 without R-protein or against type 111, irrespective of the presence of R-protein (13). These studies indicated that R-protein might be of importance for the virulence of type I1 group B streptococci.…”
mentioning
confidence: 92%